Complete manuscript title: Neurological complications from sinugenic orbital cellulitis. Issue 4 (July 2022) - Chaturvedi, Ritu; O'Rourke, Michael; Rostron, Egle; Cook, Anne; Dharmasena, Aruna
Introduction: This study was undertaken with an aim to identify any common factors or trends among patients of orbital cellulitis that developed neurological complications. Methods: A 24-month retrospective review of patients was undertaken to include those showing clinical deterioration and neurological complications on radiological imaging, after being treated for orbital cellulitis at Manchester Royal Eye Hospital. The study specifically looked at the site of orbital collection, sinus involvement, types of neurological complications and whether these were detected at initial presentation, surgical input and microbiology findings. Results: Nine patients (9/26) developed associated neurological complications during the study period. (February 2018 and January 2020) This included subdural empyema in six patients; leptomeningeal enhancement in two and septic emboli in one patient. All the patients had associated significant pan-sinusitis at initial presentation. Neurological complications were detected in three patients at the time of admission and after clinical deterioration and further investigations in the rest. Conclusion: A superior orbital abscess and Streptococcus mileri infection had higher risk of neurological complications. It is worth debating whether patients with chronic sinusitis who develop orbital cellulitis need earlier surgical input rather than a conservative treatment. Patients who fail to improve clinically need to be re-imaged to look for possible neurological complications.